2015
DOI: 10.7150/jca.12969
|View full text |Cite
|
Sign up to set email alerts
|

CT120A Acts as an Oncogene in Head and Neck Squamous Cell Carcinoma

Abstract: Squamous cell carcinoma of the head and neck (HNSCC) is among the most frequent cancers worldwide. The etiology and pathogenesis of HNSCC are influenced by multiple genetic factors in addition to environmental and lifestyle-related factors. However, the mechanism underlying the HNSCC is still far from clear.The membrane associated gene CT120 was previously identified from chromosome 17p13.3 as a lung cancer-associated gene. Its function as an activator of the Erk and Akt signaling pathways in human lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Until recently CT120 had been associated only with lung cancer 3 - 5 . In our previous report we have shown that CT120 acts as an oncogene in HNSCC 6 . Depending on our previous data we hypothesized that CT120 may have important functions in the progression of HNSCC needing further investigation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Until recently CT120 had been associated only with lung cancer 3 - 5 . In our previous report we have shown that CT120 acts as an oncogene in HNSCC 6 . Depending on our previous data we hypothesized that CT120 may have important functions in the progression of HNSCC needing further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…These results indicate that CT120 may be a key modulator in lung carcinogenesis and might contribute to the activation of oncogenic pathways in human lung cancer cells. In a previous study we have observed that the CT120A isoform is overexpressed also in head and neck squamous cell carcinoma (HNSCC) tumors 6 . However, no detailed information is available on the structural features of the CT120 gene.…”
Section: Introductionmentioning
confidence: 98%
“…FAM57A has also been linked to human carcinogenesis and both pro- and anti-tumorigenic activities have been described. For lung, liver, and head and neck cancers, FAM57A expression was reported to be increased in tumors compared to the corresponding normal tissues [ 10 , 11 , 12 , 13 , 14 ]. Interference with FAM57A expression in cell lines derived from lung and liver cancers acted anti-proliferative [ 12 , 13 , 14 ], suggesting a pro-tumorigenic role for FAM57A in these tumor entities.…”
Section: Introductionmentioning
confidence: 99%
“…A study in India reported the mutation in Rat sarcoma (Ras) gene is related to the development and progression of OSCC (Saranath et al, 1991). A more recent study reported CT120A gene as possible oncogene for HNSCC and its overexpression is associated with high tumor grades (Baltaci et al, 2015).…”
Section: Introduction and Epidemiology Of Head And Neck Cancermentioning
confidence: 99%